2021
DOI: 10.3389/fmed.2021.708432
|View full text |Cite
|
Sign up to set email alerts
|

Nailfold Capillaroscopy Abnormalities Correlate With Disease Activity in Adult Dermatomyositis

Abstract: Objectives: The aim of this study was to determine the relationship between disease activity in adult patients with dermatomyositis (DM) and other biomarkers of disease activity such as C-reactive protein creatinine kinase and nailfold video capillaroscopy (NVC).Methods: We performed a prospective single center study of 15 adult patients with DM. Study participants underwent two assessments at least 9 months apart including clinical, laboratory and NVC evaluations. Patients received immunosuppressive medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
(31 reference statements)
1
13
0
Order By: Relevance
“…The MITAX score at the onset of severe digital ischemia in patients classified as having PM/DM was comparable to the score of patients with "active disease" reported in previous studies. [50][51][52][53] Our findings stimulate further studies measuring antisynthetase antibodies in a large cohort of patients with severe digital ischemia regardless of underlying connective tissue diseases.…”
Section: Discussionmentioning
confidence: 70%
“…The MITAX score at the onset of severe digital ischemia in patients classified as having PM/DM was comparable to the score of patients with "active disease" reported in previous studies. [50][51][52][53] Our findings stimulate further studies measuring antisynthetase antibodies in a large cohort of patients with severe digital ischemia regardless of underlying connective tissue diseases.…”
Section: Discussionmentioning
confidence: 70%
“…Recent studies also showed that there are inverse correlations between NVC scores and disease activity before treatment (n = 10) and that the density can Reumatologia 2022; 60/1 be a dynamic marker of global disease activity in adult patients (n = 15) with DM that can be improved after treatment [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…There are some articles with limited numbers of patients for the evaluation of capillaroscopy in patients with OM [12,13], and a few articles pulling the patients with OM from patients with PM/DM to find the differences between these patients in their clinical and capillaroscopy features [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NFC examination is a simple method that may be used to demonstrate microvascular changes in capillaries. In clinical practice, it is mostly used as a diagnostic method in patients with systemic sclerosis and dermatomyositis with Raynaud's syndrome 7,13 . In the literature, abnormal NFC have also been found in primary vasculitides such as Behçet's disease, Henoch-Schönlein purpura, Takayasu arteritis and granulomatous polyangiitis [14][15][16][17] .…”
Section: Discussionmentioning
confidence: 99%